1986
DOI: 10.1144/gsjgs.143.6.0857
|View full text |Cite
|
Sign up to set email alerts
|

Thrust tectonics, deep structure and crustal subduction in the Alps and Himalayas

Abstract: The structural restoration of collision orogenic belts onto crustal templates provides important insights into the tectonic evolution, deep structure and amounts of plate convergence after the initial contact between two continental masses. Balanced cross-sections have been constructed, parallel to the local displacement directions, across the western Alps and western Himalayas and demonstrate very large amounts of crustal shortening above intra-crustal detachments. To achieve a balance, substantial volumes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…The eclogite-facies rocks occur 30-150 m thick shear zones surrounded by uneclogitized to partially eclogitized granulite-facies gabbroic anorthosites. The terrain, therefore, represents an example of deep continental crust partially converted to eclogite-facies during continental collision in the sense envisioned by Butler (1986) and Laubscher (1990) and affords an opportunity to study the variation of physical properties associated with this process. Austrheim and Msrk (1988) suggested that eclogite shear zones could be deep crustal reflectors because of their juxtaposition against lowervelocity granulite-facies rocks.…”
Section: "Ose I "3snmentioning
confidence: 99%
See 1 more Smart Citation
“…The eclogite-facies rocks occur 30-150 m thick shear zones surrounded by uneclogitized to partially eclogitized granulite-facies gabbroic anorthosites. The terrain, therefore, represents an example of deep continental crust partially converted to eclogite-facies during continental collision in the sense envisioned by Butler (1986) and Laubscher (1990) and affords an opportunity to study the variation of physical properties associated with this process. Austrheim and Msrk (1988) suggested that eclogite shear zones could be deep crustal reflectors because of their juxtaposition against lowervelocity granulite-facies rocks.…”
Section: "Ose I "3snmentioning
confidence: 99%
“…Crustal material may be converted to eclogite when portions of the continental crust are forced into the mantle during collisional orogenies, such as the Alpine orogeny (e.g. Butler, 1986;Laubscher, 1990;Austrheim, 1991). Laubscher (1990) cited the wellknown occurrences of eclogites with continental crustal affinities within Phanerozoic erogenic belts such as the Alps (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Their detection is therefore fundamental in the understanding of the earth's dynamic. In particular, the pres-ence of eclogite bodies within the continental lithosphere could explain high velocity patches detected in seismic tomography models or bright seismic reflectors on deep seismic reflection profiles (Butler, 1986;Laubscher, 1990;Nicolas et al, 1990;Austrheim, 1991;Warner et al, 1996). Laboratory measurements of P-and S-wave velocities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At high strain rates, the increased strength of the lower crust couples upper crust and mantle, resulting in deformation to become more distributed. Patterns of distributed deformation appear to be in disagreement with structures in recent orogens (Butler 1986), but might apply to Archean or Proterozoic tectonics (e.g. Shackleton 1993;Brun 2002).…”
Section: T E C T O N I C M O D E L Smentioning
confidence: 86%